PEMBAHARUAN HAK WARIS PEREMPUAN DI TURKI DALAM THE TURKISH CIVIL CODE PASAL 495 PERSPEKTIF MAQASID SYARI’AH - Viqi Fadilatur Rizqiyah; Sri Lumatus Sa’adah; Busriyanti Busriyanti (JURNAL HAKAM, 2026)
The reform of family law in Muslim countries often encounters tensions between classical Islamic legal norms and the demands of modernity, particularly concerning gender equality in inheritance law. Turkey represents one of the most significant examples of legal reform through the enactment of the Turkish Civil Code in 1926, which replaced the Islamic family law system with a modern civil law framework. Article 495 of the code establishes the principle of equal inheritance rights between men and women without gender discrimination. This study aims to analyze the reform of women’s inheritance rights in Turkey under Article 495 of the Turkish Civil Code from the perspective of maqasid al-shari’ah, while examining the dialectic between normative Islamic legal texts and the socio-historical context underlying the reform. This research employs a qualitative method using a normative-juridical approach combined with historical and conceptual approaches. Data were collected through library research on relevant primary and secondary legal sources. The findings indicate that although Article 495 formally differs from the distributive formula of classical Islamic inheritance law, the reform can be understood as a reinterpretation of distributive justice within the framework of maqasid al-shari’ah, particularly in terms of the protection of property (hifz al-mal) and social justice. The reform reflects an effort to adapt inheritance law to the changing social responsibilities of men and women in modern society. Therefore, the reform of inheritance law in Turkey may be viewed as a form of contextual ijtihad within modern family law policy aimed at achieving public welfare, gender equality, and substantive justice.